Laparoscopic surgery for a hydrocele of the canal of Nuck with an ovarian tumor: An extremely rare clinical finding. Issue 2 (3rd February 2022) - Tominaga, Marie; Morikawa, Kyoko; Ogawa, Yutaro; Kamimura, Naomi; Tsuneki, Ikunosuke; Tamura, Masaki; Yanase, Toru; Kobayashi, Kazuaki; Sato, Daisuke; Kameyama, Hitoshi; Iwaya, Akira; Yokoyama, Naoyuki; et al.
Abstract: This clinical image presents an unusual report of simultaneous laparoscopic resection of a hydrocele of the canal of Nuck and an ovarian tumor. Laparoscopic treatment with a proper approach is a useful technique in some cases. Abstract :